2021
DOI: 10.2166/aqua.2021.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical and trace metal qualities of rainwater in the south-eastern region of Bangladesh

Abstract: The chemical characteristics of rainwater in the south-eastern region of Bangladesh were investigated in this study in addition to identifying the potential sources of different precipitation constituents, which have often been unexplored or not well covered in the literature. Rainwater pH, major ions and trace metals were measured in samples collected from five different locations with different land-use patterns of the Chattogram Metropolitan area (CMA) during two rainy seasons. The results of this study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The obtained value of KMO was 0.667 while that of Bartlett's sphericity test was less than 0.01 implying that the studied datasets were suitable for PCA ( IBM, 2021 ). PCA is the transformation of the original variables of a data set into a set of new and uncorrelated variables which are known as the principal components (PCs), and the process is widely used to lessen data and to extract a small number of dormant factors for analysing associations among the observed variables ( Bodrud-Doza et al, 2020 ; Hossen et al, 2021 ). A component having eigenvalues of smaller than one is considered as less significant, and therefore, such an observed variable could be disregarded ( Rahman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained value of KMO was 0.667 while that of Bartlett's sphericity test was less than 0.01 implying that the studied datasets were suitable for PCA ( IBM, 2021 ). PCA is the transformation of the original variables of a data set into a set of new and uncorrelated variables which are known as the principal components (PCs), and the process is widely used to lessen data and to extract a small number of dormant factors for analysing associations among the observed variables ( Bodrud-Doza et al, 2020 ; Hossen et al, 2021 ). A component having eigenvalues of smaller than one is considered as less significant, and therefore, such an observed variable could be disregarded ( Rahman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of contaminants and the conditions in which they arise can help to develop rules, regulations, and maintenance recommendations for small-scale rainwater harvesting [26]. Common contaminants from roof runoff include zinc, copper, and iron [27], although their concentration can depend on the roofing materials, environmental factors, and rainfall characteristics [23].…”
Section: Roof Runoff Qualitymentioning
confidence: 99%
“…Regarding roofing material, some studies showed that the quality of rainwater harvested from roof runoff was greatly affected by the materials used for roofing [13,27]. The concrete roof had a beneficial influence on hardness, EC, pH, and alkalinity compared to the other roof types [29].…”
Section: Roof Runoff Qualitymentioning
confidence: 99%
See 1 more Smart Citation